Educational Planning Training For Teachers and Principals In Mataram City - Sudirman, Sudirman; Mustari, Mohamad; Asrin, Asrin; Makki, Muhammad (Pascasarjana Universitas Mataram, 2024)
Educational planning is an integrated process, which will be achieved if all parties related to the field, both government and society, have the same understanding in preparing integrated planning. This condition requires each planning unit to have human resources for planning who understand the substance of educational development and have the ability to prepare educational planning based on the conditions of each region and in accordance with structured, systematic development planning, and refer to the planning system in accordance with central government policies. The main objective of this training is to improve the technical competence of educational planning managers so that they are able to understand policies related to the basics of educational planning, statistics in educational planning, education sector diagnosis and projection techniques and simulation models in educational planning and make follow-up plans as a reference in carrying out their duties and functions as educational planners in their work units. Therefore, it is necessary to improve the competence of human resources for educational planners at the regional level. One strategy is to carry out Educational Planning Training in collaboration between local governments and local universities